Training and Physical Work Environment as Determinants of Healthcare Worker Performance - Sastro Putra , Nurul Ichza; Santoso, Teguh Iman; Krisnawati , Didin (Jurnal Minds: Manajemen Ide dan Inspirasi, 2025)
This study examines the effects of training and the physical work environment on healthcare worker performance in a hospital context. It advances human resource and performance theory by clarifying the differential explanatory power of capability development and environmental conditions, while introducing gender-based heterogeneity into the performance model. Using a quantitative causal design, data from 153 healthcare workers were analyzed through SEM-PLS. Overall performance was rated high, as were training and physical work environment conditions. Structural results indicate that both variables contribute to performance, yet gender-based analysis reveals that training does not significantly predict performance across groups, whereas the physical work environment exerts a substantially stronger effect on male employees than on female employees. These findings underscore the strategic importance of designing evidence-based, gender-sensitive HR policies to optimize healthcare workforce performance.